Simulation of electron bunch shaping and accelerating in two-section technological linac - Aizatsky, N.I.; Khodak, I.V.; Kushnir, V.A.; Mitrochenko, V.V.; Perezhogin, S.A. (Вопросы атомной науки и техники, 2000)
The paper presents the results of electron dynamics computing in the powerful resonance electron accelerator. The accelerator consists of two accelerating structures with a variable geometry and an injector including a diode electron gun, klystron type buncher and accelerating cavity. The wave phase velocity in structures is equal to the light velocity. The electron motion in the accelerator was simulated using the PARMELA code. With the 11 MW RF power supplying accelerating structures and the 1 A current at the accelerator exit the beam energy is up to 20 MeV.